The Effect of Supplementary Feeding on Body Weight of Pregnant Women Who Have Chronic Energy Deficiency in Indonesia - Hasnaini Rahmah; Andi Nurlinda; Een Kurnaesih (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Backgrounds: The high rate of infant and maternal mortality, as well as infants with low birth weight (LBW), is essentially also determined by the nutritional status of pregnant women. The purpose of this study was to determine the effect of supplementary feeding on the bodyweight of pregnant women who experience chronic energy deficiency (KEK) in the working area of ​​the Tanasitolo Health Center. Methods: This research was conducted using a Quasi-Experimental method with a Pretest-Posttest Control Group Design. The population in this study were all mothers who experienced chronic energy deficiency in the working area of ​​the Tanasitolo Health Center with a total sample of 32 mothers using consecutive sampling. The statistical test used in this study is the Paired Sample t-Test, with SPSS 20.0 Results: There was a difference in body weight (p=0.000) in KEK pregnant women before and after supplementary feeding. Conclusion: In this study, there were differences in body weight, upper arm circumference, blood pressure, and hemoglobin levels in chronic energy deficient pregnant women before and after supplementary feeding in the working area of ​​the Tanasitolo Health Center. It is hoped that the puskesmas will provide counseling about nutritional intake related to the content contained in ebi cassava crackers as a snack to optimize body weight, upper arm circumference, blood pressure, and hemoglobin levels during pregnancy.